Increasing Trend of Resistance to Penicillin, Tetracycline, and Fluoroquinolone Resistance in Neisseria gonorrhoeae from Pakistan (1992–2009). (15th September 2011) - Jabeen, Kauser; Nizamuddin, Summiya; Irfan, Seema; Khan, Erum; Malik, Faisal; Zafar, Afia
Abstract : Emergence and spread of drug resistant Neisseria gonorrhoeae is global concern. We evaluated trends of antimicrobial resistance in Neisseria gonorrhoeae over years 1992–2009 in Pakistan. Resistance rates were compared between years (2007–2009) and (1992–2006). Antimicrobial susceptibility testing was performed and interpreted according to Clinical Laboratory Standards Institute (CLSI) criteria using the disk diffusion methodology against penicillin, ceftriaxone, tetracycline and ofloxacin. Additional antibiotics tested in 100 strains isolated during 2007–2009, included cefotaxime, cefoxitin, cefuroxime, cefipime, ceftazidime, ceftizoxime, cefixime, cefpodoxime, spectinomycin and azithromycin. Neisseria gonorrhoeae ATCC 49226 was used as control. Chi-square for trend analysis was conducted to assess resistance trend over the study period. During study period significant increase in combined resistance to penicillin, tetracycline and ofloxacin was observed ( P value< 0.01 ). Resistance rates during the two study period also increased significantly ( P value< 0.01 ). Ceftriaxone resistance was not observed. None of the isolates were found to be resistant or with intermediate sensitivity to additional antibiotics. Our findings suggest that penicillin, ciprofloxacin, tetracycline should not be used in the empirical treatment of gonorrhea in Pakistan. Ceftriaxone and cefixime should be the first line therapy; however periodic MICs should be determined to identify emergence of strains with reduced susceptibility.